Respondents' challenges in implementing the Farmer FIRST Programme in Haryana - MANJEET; MALIK, JOGINDER SINGH; KUMAR, RUPENDER; KUMAR, AMRIT (The Indian Journal of Agricultural Sciences, 2026)
ICAR has launched the Farmer FIRST Programme to identify research issues, prioritise them, conduct tests, and manage them in farmer-friendly settings, focusing on Farmers' Farms, Innovations, Resources, Science, and Technology. The present study aimed to evaluate and delve into the multifaceted challenges respondents face participating in the FFP, focusing on the constraints individuals perceive within FFP-adopted villages. The study, conducted during 2019–2020 in Hisar and Karnal districts, is based on a sample of 120 farmers, 60 farmers from each district, beneficiary categories of the FFP. The constraints encountered by respondents in the successful execution of the FFP were categorised into four overarching domains: general constraints, economic constraints, organisational constraints, and communication constraints. Our analysis revealed that respondents reported varying degrees of difficulty in these domains, with mean scores of 1.79, 1.62, 1.48, and 1.55, respectively, indicating the level of constraint severity. This research provides a comprehensive insight into the challenges faced by participants in the FFP in Haryana, shedding light on specific areas where interventions and improvements are needed. The findings of this study have practical implications for policymakers, program implementers, and stakeholders, guiding them toward more effective strategies for addressing the identified constraints and optimising the impact of the FFP.